Age determination of equatorial Pacific sediments - Broecker, Wallace S; Clark, Elizabeth; Barker, Stephen; Hajdas, Irena; Bonani, Georges; Moreno, Eva (Supplement to: Broecker, WS et al. (2007): Radiocarbon age of late glacial deep water from the equatorial Pacific. Paleoceanography, 22(2), PA2206, https://doi.org/10.1029/2006PA001359, 2007)
Radiocarbon age differences for pairs of coexisting late glacial age benthic and planktic foraminifera shells handpicked from 10 sediment samples from a core from a depth of 2.8 km in the western equatorial Pacific are not significantly different from that of 1600 years calculated from measurements on prenuclear seawater. This places a lower limit on the depth of the interface for the hypothetical radiocarbon-depleted glacial age seawater reservoir required to explain the 190 per mil drop in the 14C/C for atmospheric CO2, which occurred during the mystery interval (17.5 to 14.5 calendar years ago). These measurements restrict the volume of this reservoir to be no more than 35% that of the ocean. Further, 14C measurements on a single Last Glacial Maximum age sample from a central equatorial Pacific core from a depth of 4.4 km water fail to reveal evidence for the required 5- to 7-kyr age difference between benthic and planktic foraminifera shells if the isolated reservoir occupied only one third of the ocean. Nor does the 13C record for benthic forams from this abyssal core yield any evidence for the excess respiration CO2 expected to be produced during thousands of years of isolation. Nor, as indicated by the presence of benthic foraminifera, was the dissolved oxygen used up in this abyssal water.